AMANDEMEN KE-5 UNDANG-UNDANG DASAR NRI 1945: PELUANG DAN TANTANGAN - Mustajib Mustajib; Ach. Fadlail (Fakultas Ilmu Sosial dan Humaniora, 2022)
Issues related to amendments to the Constitution, in other words, the 1945 Constitution have been widely voiced by Indonesian people, the above issues have been reported more and more recently, especially with the emergence of several ideas from political figures regarding Prioden's positions of President and Vice President as well as the postponement of the election which caused various upheavals and acceptances. negative in society. Amendments to the amendments to the Constitution are legally constitutional. Because the Indonesian Constitution is not a noble and holy one for a religion, it means that changes can be made but with a note that it is in accordance with the needs and desires of the people as the holder of the highest sovereignty in a democratic legal state. In this article, we examine the issues of change, history, challenges and opportunities to make changes to the 1945 Constitution of the Republic of Indonesia. The results of the study found that amending the 1945 Constitution is legal in accordance with the provisions of Ps. 37 paragraphs (1,2 and 3) which authorize the MPR to make changes to the Constitution. However, the challenge is that the legal politics of the above agenda is feared to result in a political compromise that benefits one party, group or class. So that an in-depth study is needed by involving many parties (the community) to participate in providing suggestions and input and considerations. The historical approach, concept and literature study were chosen as the analytical knife in this article.